Taxonomic and functional diversity of the bycatch fishes community of trawl fishing from Northern Gulf of California, Mexico. - Herrera-Valdivia, Eloísa (2016)
The Northern Gulf of California (NGC) is a mega diverse area of high endemism with major economic interest because of the multi-specific fisheries developed, mainly shrimp. There is a lack of recent studies on bycatch fish assemblages, so during the fishing seasons from 2009-2010 and 2010-2011, on board 13 shrimp boats, 14 commercial fishing trips were performed from 5 m - 90 m in depth with a total of 119 catches. The 119 catches were analyzed to assess fish community structure using taxonomic diversity indices to detect changes in the community following the taxonomic distinctness average Δ+ and the diversity index Δ* (TAXDEST of the PRIMER v6 program). To confirm the structure of functional groups, we considered similarities of ecologic and morphologic traits among species. The results showed that the indices Δ+ and Δ* were within the expected average and confidence intervals at 95%, finding significant differences between the indices. The analyses showed a well-structured community because of the great variety of forms and functions of the species within the community. In the community of the functional groups, reproduction was the ecological attribute that contributed the most to their structure. The community structure was represented by intermediate trophic levels (3-3.9), preferably primary and secondary carnivores within the trophic categories of predators of benthic ichthyo-fauna that belong to demersal species of soft bottoms and mostly fusiform body. To conclude, the NGC showed high functional redundancy according to the estimated functional groups, thus the ecosystem was considered stable and with great diversity. This type of studies should be followed using fishing and environmental effort due to the great biological and ecologic importance in the area.